COPING STRATEGIES USED BY ONCOLOGY PALLIATIVE CARE NURSES: AN INTEGRATIVE REVIEW - Naira Agostini Rodrigues dos Santos; Suelen Veras Gomes; Clarice Maria de Araujo Rodrigues; Juliano dos Santos; Joanir Pereira Passos (Universidade Federal do Paraná, 2016)
The aim of this study was to characterize the coping strategies used by nurses who provide palliative care to cancer patients. This is an integrative review, with literature search in the months of March and April 2015, in healthcare databases. Thirteen articles meeting the inclusion criteria in the period from 1995 to 2015 were selected. The results showed coping strategies based on the problem, including problem solving, improvement of scientific and technical knowledge, and strategies focused on emotion, which are related to religiosity, spirituality and social support from family and colleagues. It was concluded that building effective coping strategies can make work more enjoyable, reduce occupational risks, and improve management indicators and the quality of care provided to patients.